Hubungan antara Quality of Work Life dengan Kinerja Guru di Sekolah Menengah Pertama Negeri Kecamatan Pulogadung Kota Administrasi Jakarta Timur - Rifky Audrey Maulana; Neti Karnati; Winda Dewi Listyasari (Program Studi Manajemen Pendidikan, 2017)
This study aims to determine whether there is a relationship between the qualityof work life and teachers performance of Junior High School in Pulogadung DistrictArea, East Jakarta. This research is a quantitative study with 2 variables in it, namely:(X) Quality of Work Life as independent variables and (Y) Performance as the dependentvariable. Quality of work life is a set of real work situations in organizations which refersto the creation of performance improvement, employee involvement, as well as thesatisfaction of the people involved in the organization in order to meet the expectations ofthe members of the organization. Performance is the attitude of the person which gift acontribution to reach the goal of work and the purpose of organization. The method usedis survey method with the results of correlational studies. The population in this study is aJunior High School teacher in Pulogadung District Area, East Jakarta. Samples weretaken by using a simple random sampling technique. The technique is based on thesample size used in this study were 65 teachers. Data collection for the variable QualityOf Work Life (X) and Performance (Y) using a questionnaire. Product MomentCorrelation coefficients obtained, the coefficient r equal to 0.61079, and the results oftesting the hypothesis with t test obtained t count equal to 6.123 is greater than t table of1.669, then the alternative hypothesis (Ha) is expressed in a significant correlationcoefficient received. The coefficient of determination of 0.3731 this means that thecontribution of the quality of work life in schools to performance of Junior High Schoolteacher in Pulogadung District Area, East Jakarta, amounting to 37.31%.